A VP-internalresultative analysis of 4 "VP-external" uses of Slavic verbal prefixes - Zaucer, Rok (University of Ottawa (Canada), 2009)
This thesis is about the structure of prefixed verbs in Slavic and the syntax of resultative secondary predication. The topic is explored through four case studies of different prefixed-verb constructions (Slovenian na-laufati se [on-run self] 'get one' s fill of running', Slovenian/Russian na-brati/na-brat' [on-gather] 'gather a quantity of, Slovenian pre-sedeti [through-sit] and Russian pro-sidet' [through-sit] 'spend time sitting'). The discussion is cast against the often hypothesized distinction between VP-internal/resultative and VP-external prefixes, for which all four constructions present a puzzle. For example, some of the prefixes in these constructions can stack on a verbal base that already contains a VP-internal/resultative prefix, which is typically considered a diagnostic of VP-externality. On the other hand, these same prefixes also change the argument structure of their input, which is the hallmark of resultative secondary predication. The thesis argues that the constructions discussed all contain VP-internal/resultative prefixes. This conclusion opens another puzzle: when these prefixes stack over another resultative prefix, we have two resultative prefixes on one verbal root. This appears to go against the widely-assumed hypothesis that there can be only one resultative secondary predicate per verb. The thesis reconciles this hypothesis with the investigated data by proposing that, surface appearances notwithstanding, the syntactic structure of such doubly-prefixed 'verbs' in fact contains two VPs, each of which embeds a prefix-headed resultative secondary predicate; one of the V' s, however, is null. The postulation of two VPs is supported with various kinds of novel data, including adverbial modification, aspectual patterning, and the occurrence of two unselected objects. The two VPs are proposed to be concatenated in a manner similar to one that has been proposed for some serial verb constructions, in a conjunction-like structure under a single Tense node. The results of the thesis have consequences for the general theory of resultative secondary predication, for the theory of null verbs, and for the often hypothesized distinction between VP-internal/resultative and VP-external prefixation in Slavic.
Keywords: Language, Linguistics.; Literature, Slavic and East European.